The battle for WondLa - DiTerlizzi, Tony (DiTerlizzi, Tony. Wondla trilogy, 2014)
When all hope for a peaceful coexistence between humankind and aliens seems lost, Eva Nine, with help from an unlikely ally, tries to thwart the evil Loroc's ultimate plan for life on Orbona.